The Association of Thyroid Nodules With Blood Trace Elements Identified in a Cross-Section Study - Zeng, Huixian; Hu, Yuanyuan; Luo, Yaosheng; Ye, Yanshi; Song, Cheng; Yu, Genfeng; Chen, Zhi; Liu, Siyang; Liang, Yongqian; Liu, Lingling; Wan, Heng; Shen, Jie (Frontiers in Nutrition, 2022)
Background The association between occurrence of thyroid nodules (TNs) and trace elements detectable in blood are still inconclusive. The present study sought to determine the relationship between selected trace elements and TNs in the iodine-adequate area of Guangdong, China. Methods A total of 1,048 participants from four communities were enrolled. A number of medical checkups were conducted to collect relevant data on anthropometric parameters, blood pressure, glucose blood levels and lipid profiles, as well as data on thyroid function, presence of thyroid autoantibodies, and trace elements. Presence of TN was diagnosed by ultrasonography. Results Of the 1048 participants (49.5 ± 14.4 years old), 543 participants (51.8%) had TNs. Serum copper, magnesium and zinc levels are associated with the presence of TNs among healthy subjects. Subjects with higher levels of zinc, magnesium and copper had 1.23-fold, 1.04-fold, and 1.007-fold increased risks of the prevalence of TNs (P = 0.013, 0.017, and < 0.001, resp). Compared with the first quartile of copper content in serum, participants in the fourth quartile had the highest prevalence of TNs with an odds ratio of 8.90 (95% confidence interval (CI) 5.41, 14.94) among all participants. Women in the third quartile of magnesium level had a 1.86-fold (95%CI 1.05, 3.31) risk of the prevalence of TNs. Subjects in the highest quartile of zinc level had a 1.82-fold (95%CI 1.06, 3.16) risk of the prevalence of TNs in females. Conclusion TNs were found highly prevalent in females in the investigated population from an iodine-adequate area of Guangdong, China. The imbalance of selected trace elements (copper, magnesium and zinc) in the body is related to the presence of TNs among healthy subjects. The observed correlation of copper on TNs warrants further studies.